Complete Covid-19 Vaccination and Room Occupation Rates Nexus Tourism in East Java: Big Data Approach - Agus Muslim; Eko Aprianto (East Java Economic Journal, 2023)
The purpose of this study is to examine the effect of complete vaccination up to the second dose on the mobility of the population to recreational and retail areas that describe tourism activities, to examine the effect of population mobility to recreational and retail areas on the occupancy rate of hotel rooms and to examine the factors that influence the level of high and low the rating value of a hotel or other accommodation service that describes the level of satisfaction with hotel services in East Java. Inferential statistical methods used are time series analysis with ARIMAX, Pearson Correlation Analysis and Ridge Regression Analysis. The data used is a combination of Big Data and Official Statistics. Big Data is obtained from scrapping results in Google Mobility Index (GMI), the Ministry of Health of the Republic of Indonesia, and www.tiket.com as well as official statistics sourced from the Central Boards of Statistics Indonesia (BPS). Based on the results of ARIMAX, it can be concluded that complete vaccination up to the second dose affects the mobility of the population to recreational and retail areas that indicate tourism activities, then based on the results of the Pearson correlation, it can be concluded that there is a strong and positive correlation between the mobility of residents to recreational areas and room occupancy rates hotels in East Java and based on the Ridge Regression analysis, it can be concluded that there is a positive influence of price appropriateness, cleanliness, service, facilities, and location on consumer ratings that describe the level of satisfaction with hotel services in East Java and the dimension that has the most influence on the level of hotel satisfaction in East Java is price appropriateness